Qualitative comparison of fermented drinks from wort obtained from fermentation of germinated unpolished purple rice with and without addition of commercial enzymes - Surayot, Utoomporn; Jomduang, Somchai (Food and Applied Bioscience Journal, 2017)
This research aimed to compare quality of the fermented drinks obtained from the germinated unpolished purple rice. The unpolished purple rice grains (Kum Doi Saket variety) were soaked in water at 40°C for 3 h and then the grains were allowed to germinate at 35°C for 56 h. The germinated rice were grounded with water at the ratio of 30:70 and then hydrolyzed to produce wort using two methods: germinated rice’s enzyme hydrolysis and germinated rice’s enzyme combined with commercial enzyme hydrolysis (Termamyl SC and SAN Super 360 L). It was found that wort from the second method had significantly (p<0.05) higher total soluble solid than that obtained from the first method (30.13±0.5118.77±0.25 and 18.77±0.25°Brix, respectively). After that, the wort was fermented at ambient temperature, using dry active yeast (Fermiblanc). The fermented wort from germinated rice’s enzyme hydrolysis had 2.20±0.14% alcohol content. Low alcoholic fermented drink was prepared by mixing the fermented wort with the unfermented germinated rice’s enzyme hydrolysis wort to adjust the alcohol content to 0.5%. Sugar was added to obtain 14°Brix of total soluble solid. The liquid was filled into glass bottle before boiling. On the other hand fermented wort produced from the second method of hydrolysis had 9.00±0.10% alcohol content. After that, it was prepared for high alcoholic fermented drink by siphoning and filling into glass bottle. Qualitative analysis of the two fermented drinks showed that the low alcoholic fermented drink contained higher gamma-aminobutyric acid (GABA) and cyaniding-3-glucoside, but gamma-oryzanol was not found in both drinks. The sensory acceptance by 50 panelists showed that all of them preferred the low alcoholic fermented drink because of its beautiful red color, good aroma and taste.